Age Differences in Open-Mindedness: From 18 to 87-Years of Age. Issue 1 (1st January 2022) - Edgcumbe, Daniel R.
ABSTRACT: Background: As health care improves and more people work into later age, it is important to understand what impacts open-mindedness has on decision-making. This paper examined the role of aging on open-mindedness. Methods: Open-mindedness was measured across 12 studies before data amalgamation. The Actively Open-minded Thinking (AOT) scale and Actively Open-minded Thinking about Evidence (AOT-e) scale measured open-mindedness in this sample (n = 9010) of participants between 18 and 87-years of age. Results: Summary AOT positively correlated with AOT-e (r = 0.27). For two subfactors derived from factor analysis based on the AOT, scores for both subfactors positively correlated with AOT-e (subfactor-1: r = 0.17/subfactor-2: r = 0.31) but negatively correlated with age (subfactor-1: r = −0.01/subfactor-2: r = −0.16). Age negatively correlated with both AOT (r = −0.11) and AOT-e (r = −0.13). Regressions revealed that open-mindedness decreased with aging. Age marginally predicted the change in open-mindedness, and sex differences were not a predictor. Conclusion: It is proposed that the observed differences are the result of a reluctance to change long-established values and ideas at the cognitive level and cortical changes that occur with aging. In an aging population where more adults work into later age, the decrease in open-mindedness could influence many areas of judgments of decision-making. Importantly, this demonstrates that open-mindedness varies across lifespan.